2020
DOI: 10.1186/s13023-020-01445-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, pathological, imaging, and genetic characterization in a Taiwanese cohort with limb-girdle muscular dystrophy

Abstract: Background: Limb-girdle muscular dystrophy (LGMD) is a genetically heterogeneous, hereditary disease characterized by limb-girdle weakness and histologically dystrophic changes. The prevalence of each subtype of LGMD varies among different ethnic populations. This study for the first time analyzed the phenotypes and genotypes in Taiwanese patients with LGMD in a referral center for neuromuscular diseases (NMDs). Results: We enrolled 102 patients clinically suspected of having LGMD who underwent muscle biopsy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Several unique frequent mutations were found in our cohort.A founder mutation, c.545A > G in FKRP was detected in 44 compound heterozygous patients and 10 homozygous patients. It was also found as frequent mutations in the LGMD cohort in a Taiwanese study 27 . It was different from the common mutation c.826C > A (p.Leu276Ile) in European countries, 28,29 the USA 23 and Brazil 24 .…”
Section: Discussionmentioning
confidence: 78%
“…Several unique frequent mutations were found in our cohort.A founder mutation, c.545A > G in FKRP was detected in 44 compound heterozygous patients and 10 homozygous patients. It was also found as frequent mutations in the LGMD cohort in a Taiwanese study 27 . It was different from the common mutation c.826C > A (p.Leu276Ile) in European countries, 28,29 the USA 23 and Brazil 24 .…”
Section: Discussionmentioning
confidence: 78%
“…Bayesian analysis suggests that dysferlinopathy, α-sarcoglycanopathy (R3), and anoctaminopathy may have higher prevalence rates than population studies have shown, especially considering the diagnostic challenges with later onset and more slowly progressing disease [ 30 ]. The other LGMD subtypes generally are uncommon but may manifest more frequently in areas with founder effect, e.g., telethoninopathy (R7) in Taiwan (Table 4 ) [ 24 , 31 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…The other LGMD subtypes generally are uncommon but may manifest more frequently in areas with founder effect, e.g., telethoninopathy (R7) in Taiwan (Table 4 ) [ 24 , 31 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Due to the genetic heterogeneity, LGMD diagnosis often remains, nonetheless, a complicated task to this day. A large retrospective study in clinically diagnosed LGMD found that protein expression studies were imperative to judge the causative nature of variants [45].…”
Section: Conclusive Diagnosis Of Lgmd Necessitates Pinpointing Of the Causal Gene Defectmentioning
confidence: 99%